Transcavernosal transmekkel access in surgery of hard-to-reach basilar artery aneurysms - R. N. Lunkova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
The manuscript provides clinical and anatomical rationale for interventions on hard-to-reach skull base aneurysms from transcavernosal access. The impact of basal surgery improved the capabilities of the accesses used in vascular neurosurgery, provided an overview of the hard-to-reach segment of the ACBM and the quality of aneurysm clipping. The low location of the BA apex, fetal type of structure, short size of the VAS and anatomical characteristics of the aneurysm (AA with dome direction to intercostal fossa, calcified AA walls, aneurysm with wide neck) complicate the use of pterional access. For anterolateral accesses the problem of surgical target view from the selected interspace, one of the boundaries of which is the ACA (optico-carotid, carotid-oculomotor interspace) remains. The problem of temporal lobe traction damage during surgical intervention has not been solved for lateral accesses. The proposed variant of trans-mechanteric transcavernosal access with resection of lateral parts of the upper scape, the apex of the temporal bone pyramid and destruction of the Dorello channel in the area of the described "postero-medial triangle of the skull base" opens the scape I zone and allows basal approach to the BA trunk and apex, especially at its low location.